Comparative study of composite single crystal and polycrystalline YAG:Ce phosphors for laser-based lighting applications - M Chakraborty; Md Mahmudul Hasan; W M Jadwisienczak; F Rahman (JPhys Photonics, 2024)
YAG:Ce, a widely employed phosphor for LED wavelength conversion applications, comes in different forms, including polycrystal (powder), single crystal, and composite single crystal varieties. We investigated Epoch Neo ^TM , a composite single crystal incorporating Al _2 O _3 as a heat distribution and optical guiding material embedded within its luminescent core. The properties of Epoch Neo were analyzed and compared with those of its polycrystal counterparts in this paper. Multiple characterization techniques like chromaticity points, color temperature, phosphor temperature, and speckle pattern were employed to study the effect of variable laser input power on both polycrystal powder and composite single crystal of YAG:Ce. It was found that under the influence of pumping blue laser high input optical power the composite single crystal phosphor’s performance was significantly better compared to that of the polycrystal.